2021
DOI: 10.29303/akurasi.v4i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Peran Reward dan Komitmen Organisasi Terhadap Niat Whistleblowing: Sebuah Studi Eksperimen

Abstract: Studi ini bertujuan untuk menguji peran penghargaan (reward) dan komitmen organisasi terhadap niat whistleblowing, dan peran reward terhadap niat whistleblowing ketika anggota organisasi memiliki komitmen organisasi yang rendah. Penelitian ini menggunakan model eksperimen tulen dengan partisipan mahasiswa Program Studi Akuntansi Syariah. Design eksperimen yang digunakan adalah between subject 2x2. Hasil diperoleh dari penggunaan Analisis Varian (ANOVA). Penelitian ini menghasilkan tiga temuan. Pertama, hasil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…Organizations, both private and public, may consider establishing whistleblowing policies or regulations, as well as rewards for potential whistleblowers or whistleblowers, as well as developing and strengthening human resources in terms of rewards and organizational commitment. This research's findings are consistent with those of the Azzahrah & Hadinata (2021) research, which discovered that the interaction between organizational commitment and rewards has a positive influence on whistleblowing intentions because organizational members are motivated to whistleblower when there are rewards.…”
Section: Hypothesis Test Results (T-test) and Discussion Of Research ...supporting
confidence: 89%
“…Organizations, both private and public, may consider establishing whistleblowing policies or regulations, as well as rewards for potential whistleblowers or whistleblowers, as well as developing and strengthening human resources in terms of rewards and organizational commitment. This research's findings are consistent with those of the Azzahrah & Hadinata (2021) research, which discovered that the interaction between organizational commitment and rewards has a positive influence on whistleblowing intentions because organizational members are motivated to whistleblower when there are rewards.…”
Section: Hypothesis Test Results (T-test) and Discussion Of Research ...supporting
confidence: 89%
“…Rewards can also affect the intention to do whistleblowing because the reward is one of the factors related to whistleblowing, where If someone receives a reward for acting with good intent, that person's intentions will be influenced [10]. Research conducted by [22], and [9] found that rewards affect the intention to do whistleblowing. These findings are proven by the research of [23], [24], [20], and [25] which found that rewards have a positive effect on the motive of engaging in whistleblowing.…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai kecurangan yang dilakukan dalam waktu yang bersamaan atau dalam keadaan terorganisir seringkali menimbulkan dampak negatif tidak hanya bagi orang-orang di dalam lembaga, tetapi juga pada semua pihak eksternal, dalam hal ini contohnya yaitu masyarakat Dewi et al, (2021). Dengan demikian, whistleblowing dapat menjadi cara penting untuk meningkatkan efektivitas suatu organisasi Cheng et al, (2019), terlepas dari siapa yang melaporkan kecurangan tersebut, mekanisme yang tepat harus tersedia untuk mendeteksi kecurangan melalui pelaporan pelanggaran Hadinata & Mustika Azzahrah, (2021). Internal Whistleblowing Intention merupakan suatu niatan yang timbul atau muncul dari seorang pegawai atau individu suatu organisasi untuk melaporkan sebuah tindakan yang melawan hukum kepada individu lain ataupun kepada atasannya didalam organisasi tersebut.…”
unclassified